Characterization of the complete mitochondrial genome of Spirometra decipiens (Cestoda: Diphyllobothriidae) from China. Issue 2 (3rd July 2019) - Xie, Yue; Li, Yingxin; Gu, Xiaobin; Zhang, Senzhao; Liu, Yunjian; Wang, Lu; Zheng, Youle; Zhou, Xuan; Zuo, Zhicai; Yang, Guangyou
Abstract: The plerocercoid larvae (spargana) of Spirometra decipiens (Cestoda: Diphyllobothriidae) can parasitize humans, causing the zoonotic sparganosis. In this study, the complete mitochondrial genome of this tapeworm was determined using an Illumina sequencing platform. The entire genome was 13, 642 bp in length and contained 12 protein-coding genes, 22 transfer RNAs, two ribosomal RNAs, and two non-coding regions. The phylogeny indicated that S. decipiens was closely related to Spirometra erinaceieuropaei and supported the monophyletic relationships between Spirometra, Diphyllobothrium, and Diplogonoporus within the Dipyllobothriidae. These results should contribute to a better understanding of the phylogenetic position of this species.